In vitro and In vivo evaluation of streptomyces suppressions against anthracnose in chili caused by colletotrichum - Pedram Shahbazi; Md. Yusoff Musa; Geok, Yuan Annie Tan; Farhat Ahmadi Avin; Wee, Fei Aaron Teo; Vikineswary Sabaratnam (Universiti Kebangsaan Malaysia, 2014)
The isolation of 66 streptomycetes from rhizosphere soil of chili plants was done for their inhibitory activities against three different dominant species of Colletotrichum namely C. acutatum, C. gloeosporioides and C. capsici. Twenty one streptomycetes strains were active against at least one of the Colletotrichum species. In addition, ten strains that inhibited the in vitro growth of Colletotrichum species showed chitinase activity. Strain P42, which displayed the highest inhibitory activity against all three anthracnose fungi species and high chitinase activity was tested as biological control agent in a greenhouse study. The strain successfully controlled chili anthracnose disease by significantly reducing the disease severity. Phylogenetic analysis of the 16S rRNA gene sequences showed that strain P42 belongs to the Streptomyces rochei clade. The results of the current study showed that rhizosphere-derived soil of chili plants is an important source of bioactive streptomycetes which are antagonistic against Colletotrichum.